Compounds from the pods of Astragalus armatus with antioxidant, anticholinesterase, antibacterial and phagocytic activities. (1st December 2016) - Labed, Amira; Ferhat, Maria; Labed-Zouad, Ilhem; Kaplaner, Erhan; Zerizer, Sakina; Voutquenne-Nazabadioko, Laurence; Alabdul Magid, Abdulmagid; Semra, Zahia; Kabouche, Ahmed; Kabouche, Zahia; Öztürk, Mehmet
Abstract: Context: The phytochemical study and biological activities of Astragalus armatus Willd. subsp. numidicus (Fabaceae) pods, an endemic shrub of Maghreb, are reported. Objective: This study isolates the secondary metabolites and determines the bioactivities of Astragalus armatus pods. Materials and methods: The chloroform, ethyl acetate and n -butanol extracts of hydro-ethanolic extracts were studied. Antioxidant activity was investigated using DPPH and ABTS radical scavenging, CUPRAC and ferrous chelating assays at concentrations ranging from 3 to 200 μg/mL. Anticholinesterase activity was determined against acetylcholinesterase and butyrylcholinesterase enzymes at 50, 100 and 200 μg/mL. Antibacterial activity was performed according to minimum inhibitory concentration (MIC) method. Carbon clearance method in albino mice was used for the phagocytic activity at concentrations 50, 70 and 100 mg/kg body weight. Spectroscopic techniques were used to elucidate the compounds. Results: Ethyl acetate extract afforded a flavonoid (1 ) while the n -butanol extract gave four flavonoids (2–5 ), a cyclitol (6 ) and a cycloartane-type saponin (7 ). The ethyl acetate extract exhibited highest antioxidant activity in DPPH (IC50 : 67.90 ± 0.57 μg/mL), ABTS (IC50 : 11.30 ± 0.09 μg/mL) and CUPRAC (A0.50 : 50.60 ± 0.9 μg/mL) assays. The chloroform extract exhibited the best antibacterial activity against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa, each with 80 μg/mL MIC values. The n -butanol extract enhanced phagocytic activity. Discussion and conclusion: Isorhamnetin (1 ), isorhamnetin-3- O -α-l -rhamnopyranosyl-(1 → 6)-β-d -galactopyranoside (2 ), isorhamnetin-3- O -β-d -apiofuranosyl-(1 → 2)-[α-l -rhamnopyranosyl-(1 → 6)]-β-d -galactopyranoside (3 ), kaempferol-3- O -(2, 6-di- O -α-l -rhamnopyranosyl)-β-d -galactopyranoside (4 ), kaempferol-3- O -(2, 6-di- O -α-l -rhamnopyranosyl)-β-d -glucopyranoside (5 ), pinitol (6 ) and cyclomacroside D (7 ) were isolated whereas1, 2, 6 and7 are reported for the first time from A. armatus.